Pengaruh Lingkungan Kerja Fisik dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Cedefindo Bekasi - Darmadi Darmadi; Marindi Yesi Oviyanto (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance is a critical factor in achieving organizational goals, and it is influenced by various internal and external factors, including the physical work environment and work motivation. In many companies, inadequate workplace facilities and low employee motivation can hinder productivity and overall performance. This study aims to examine the individual and combined effects of the physical work environment and work motivation on employee performance at PT. Cedefindo Bekasi. The research employs a quantitative approach with an associative method. The population consists of 60 employees, and data collection was conducted using a census sampling technique. Primary data were obtained through structured questionnaires with closed-ended questions measured on a Likert scale. The collected data were analyzed using SPSS 27 and processed with multiple linear regression, following stages of descriptive analysis, validity and reliability testing, classical assumption testing, and hypothesis testing. The findings indicate that both a supportive physical work environment and high work motivation have significant positive effects on employee performance individually and jointly. These results highlight the importance of improving workplace facilities and fostering employee motivation through effective policies, recognition, and managerial support. Enhancing these factors can increase employee productivity, contributing to organizational success. The study provides practical implications for management to develop strategies that promote employee well-being and optimize overall performance.